2005
DOI: 10.1111/j.1523-1755.2005.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and albumin as predictors of all-cause and cardiovascular mortality in chronic kidney disease

Abstract: Both high CRP and low albumin, measured in CKD stages 3 and 4, are independent risk factors for all-cause mortality. High CRP, but not serum albumin, is a risk factor for cardiovascular mortality. These results suggest that high CRP and hypoalbuminemia provide prognostic information independent of each other in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
236
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(268 citation statements)
references
References 46 publications
14
236
1
11
Order By: Relevance
“…29 Inflammation and oxidative stress have been linked to the pathogenesis of plaque formation and plaque rupture, 30 both of which are associated with worse cardiovascular outcomes. 31 The present study found no differences in traditional risk factors between patients with and without cardiac events. Higher CRP levels were associated with cardiac events at 3 years of follow-up, but not after 1 year.…”
Section: Discussionmentioning
confidence: 52%
“…29 Inflammation and oxidative stress have been linked to the pathogenesis of plaque formation and plaque rupture, 30 both of which are associated with worse cardiovascular outcomes. 31 The present study found no differences in traditional risk factors between patients with and without cardiac events. Higher CRP levels were associated with cardiac events at 3 years of follow-up, but not after 1 year.…”
Section: Discussionmentioning
confidence: 52%
“…A albumina sérica foi o único parâmetro laboratorial analisado neste estudo, por ser ainda associada ao maior risco de mortalidade, embora alguns estudos sugiram que a proteína C-reativa seja um preditor primário dos níveis de albumina sérica em pacientes em hemodiálise (38). Estudos de Kubrusly et al, 2012, sugere que seja dosada albumina pós-diálise como melhor marcador do estado nutricional e de risco de mortalidade em pacientes com desnutrição leve ou risco nutricional, por apresentar menor confundimento de interpretação pela influência do estado de hiper-hidratação pré-diálise (39).…”
Section: Resultsunclassified
“…Low serum albumin was defined as serum albumin Ͻ3.5 mg/dl (18 -20). Elevated CRP was defined as Ͼ3.0 mg/dl (21,22).…”
Section: Variablesmentioning
confidence: 99%